2020
DOI: 10.1016/j.sjbs.2020.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic activity of melittin with mupirocin: A study against methicillin-resistant S. Aureus (MRSA) and methicillin-susceptible S. Aureus (MSSA) isolates

Abstract: Methicillin-Resistant Staphylococcus aureus (MRSA) biofilms are involved in various nosocomial infections, being in the limelight of academic research. The current study aimed to determine the antimicrobial effects of melittin on planktonic and biofilm forms of S. aureus . Following the identification of MRSA and SCCmec types (using PCR method), Minimum Inhibitory Concentration (MIC), Minimum Bactericidal Concentration (MBC), and fractional inhibitory concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…The results showed melittin had antibacterial activities against these tested strains, particularly, melittin showed high activity against S. aureus and A. baumannii (Table 1). It is worth noting that melittin has antibacterial activity against Gram-positive and Gram-negative bacteria, which again proves that melittin has a broad spectrum of antibacterial effects as previously reported [33,34]. E. coli, S. aureus, P. aeruginosa, and A. baumannii are particularly important in human and veterinary medicine due to their pathogenicity, virulence, distribution, diversity of clinical signs, and problems related to public health.…”
Section: Discussionsupporting
confidence: 75%
“…The results showed melittin had antibacterial activities against these tested strains, particularly, melittin showed high activity against S. aureus and A. baumannii (Table 1). It is worth noting that melittin has antibacterial activity against Gram-positive and Gram-negative bacteria, which again proves that melittin has a broad spectrum of antibacterial effects as previously reported [33,34]. E. coli, S. aureus, P. aeruginosa, and A. baumannii are particularly important in human and veterinary medicine due to their pathogenicity, virulence, distribution, diversity of clinical signs, and problems related to public health.…”
Section: Discussionsupporting
confidence: 75%
“…We speculated that was because TCA can destroy the biofilm and cell membrane of MRSA. The results of the biofilm inhibition assay indicated that TCA can significantly inhibit the biofilm formation and the expression of the biofilm regulatory gene hld [ 14 ]. The biofilm of MRSA has serious clinical implications, making it difficult to eradicate and more tolerant to antibiotic therapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Then, 200 μL of crystal violet (1 % concentration) was added to each well. OD570 was assessed using an ELISA Reader Stat Fax2100 (Awareness Technology, Ukraine) following the addition of 200 μL of acetic acid (33 %) [47] . The results of the biofilm formation were categorized into the following groups:…”
Section: Methodsmentioning
confidence: 99%